Control de ingresos en las ventas de productos agrícolas en la empresa Agroxven S.A. de la ciudad de Ventanas - Puga Vera, Andrés Antonio (2021)
This research was carried out at the company Agroxven SA, from the city of Ventanas, dedicated to the export of poop and fine aroma coffee, in addition to commercializing various agricultural products such as rice, soybeans and corn with high quality standards that contribute to meeting the needs of demand. The objective of the study was to evaluate the control of income from the sale of agricultural products, since it presents weaknesses in its financial management, due to the fact that there are processes that are executed in an informal and empirical way that condition the fulfillment of the planned objectives. . The applied methodology was constituted by a mixed approach, accompanied by the type of exploratory and descriptive research that by using the deductive and inductive method it was possible to analyze and describe in detail the particular situations of the raised topic. For this reason, interview techniques aimed at the company's sales team and an internal control survey were used to assess the level of confidence of the sales department. The results were that there are commercial operations that are carried out informally, such as purchase settlements and others that do not have documentary support, this means that financial management does not have up-to-date and reliable information. In addition, the organization lacks a department in charge of controlling economic transactions, which is why its level of trust is low and the risk of control is high, which is an indicator that internal processes are carried out poorly.